Handbook of Positive Behavior Support - Sailor, W. (Springer, 2017)
A revolution in working with difficult students began during the 1980s, with a dramatic shift away from dependence on simply punishing bad behavior to reinforcing desired, positive behaviors of children in the classroom. With its foundation in applied behavior analysis (ABA), positive behavior support (PBS) is a social ecology approach that continues to play an increasingly integral role in public education as well as mental health and social services nationwide.